Questions and deception: How to ask better questions and elicit the truth. (October 2022) - VanEpps, Eric M.; Hart, Einav
Abstract: Questions are important tools for uncovering information, but to avoid deception, question askers must be strategic in what and how they ask—and consider the social implications of their questions. Askers should consider that in addition to soliciting information, questions also signal information about expected answers, askers' own knowledge, and the parties' relationship. We review literature on deception, conversations, and impression management to discuss signals embedded in question phrasing, and how these signals affect the truthfulness of respondents' disclosures. Askers can increase truthful disclosure by remaining neutral about the desirability of possible responses, conveying knowledge of the topic, and signaling trust. We identify how asking better questions requires being more cognizant of the informational and relational signals that questions send.